Personalized alignment in total knee arthroplasty: current concepts - Lustig Sébastien; Sappey-Marinier Elliot; Fary Camdon; Servien Elvire; Parratte Sébastien; Batailler Cécile (SICOT-J, 2021)
Traditionally in total knee arthroplasty (TKA), a post-operative neutral alignment was the gold standard. This principle has been contested as functional outcomes were found to be inconsistent. Analysis of limb alignment in the non-osteoarthritic population reveals variations from neutral alignment and consideration of a personalized or patient-specific alignment in TKA is challenging previous concepts. The aim of this review was to clarify the variations of current personalized alignments and to report their results. Current personalized approaches of alignment reported are: kinematic, inverse kinematic, restricted kinematic, and functional. The principle of “kinematic alignment” is knee resurfacing with restitution of pre-arthritic anatomy. The aim is to resurface the femur maintaining the native femoral joint line obliquity. The flexion and extension gaps are balanced with the tibial resection. The principle of the “inverse kinematic alignment” is to resurface the tibia with similar medial and lateral bone resections in order to keep the native tibial joint line obliquity. Gap balancing is performed by adjusting the femoral resections. To avoid reproducing extreme anatomical alignments there is “restricted kinematic alignment” which is a compromise between mechanical alignment and true kinematic alignment with a defined safe zone of alignment. Finally, there is the concept of “functional alignment” which is an evolution of kinematic alignment as enabling technology has progressed. This is obtained by manipulating alignment, bone resections, soft tissue releases, and/or implant positioning with a robotic-assisted system to optimize TKA function for a patient’s specific alignment, bone morphology, and soft tissue envelope. The aim of personalizing alignment is to restore native knee kinematics and improve functional outcomes after TKA. A long-term follow-up remains crucial to assess both outcomes and implant survivorship of these current concepts.